How Does Public Debt Change when the Next Crisis Comes - and It Will Come!/the Expected Evolution of Greece's State Debt in the Next Crisis Period/ - Török, László (International Journal of Engineering and Management Sciences, 2018)
It has recently been announced that Greece may withdraw from the Euro-Zone permanent rescue fund's aid program because it has successfully met the conditions imposed on it. Creditors and credit qualifiers also agreed that the Greek economy was on a good growth path. That is why there is a chance that by 2030 the current sovereign gross debt of 182.7 per cent of GDP will fall to 123.3 per cent. The author finds this statement unfoundedly optimistic. He argues that the Greek debt ratio – despite the current optimum economic fundamentals – does not seem to be sustainable. He sees greater probability that in the near future it will again be necessary to release some of the Greek debt. Debt reduction will also mean a new orderly state bankruptcy. The study seeks to highlight how vulnerable and risked the sustainability of current Greek debt financing. Using a macroeconomic model, it shows and justifies how the Greek sovereign debt changes in the case of a crisis that is only half the extent of the previous subprime crisis. If this happens, by 2023, the state debt will rise to more than double the national product, and by 2030 only to the present, otherwise critical, level. It follows that the high risk of financing Greek state debt remains unchanged.